Infrared thermography study of the fatigue crack propagation - A.Yu. Fedorova; M.V. Bannikov; M.V. Bannikov; O.A. Plekhov; E.V. Plekhova (Fracture and Structural Integrity)
The work is devoted to the experimental study of heat dissipation process caused by fatigue crack propagation. To investigate a spatial and time temperature evolution at the crack tip set of experiments was carried out using specimens with pre-grown centered fatigue crack. An original mathematical algorithm for experimental data treatment was developed to obtain a power of heat source caused by plastic deformation at crack tip. The algorithm includes spatial-time filtration and relative motion compensation procedures. Based on the results of mathematical data treatment, we proposed a way to estimate the values of J-integral and stress intensity factor for cracks with pronounced the plastic zone.